Forced Displacement : Overview of the World Bank Portfolio - Gomez, Margarita Puerto; Christensen, Asger; Harild, Niels (World Bank, Washington, DC, 2012)
For the purposes of this note, forced displacement refers to the situation of persons who are forced to leave or flee their homes due to conflict, violence, or persecution. Those displaced can either be refugees outside their country of nationality or be people displaced inside their country of nationality (IDPs). This notwithstanding, the portfolio review of Bank activities addressing displacement indicates a need for systematically incorporating information on displaced (both people in displacement and returnees) in the household income surveys that provide the data for the poverty assessments, which in turn furnish critical information for poverty reduction strategies and the different types of country assistance strategy documents. If and when information is available on the poverty situation of displaced households and the specific needs and vulnerabilities of those displaced compared to other poor groups, it will be possible to assess the need for additional analytical work or activities across the wide spectrum of operations, where the Bank has previously addressed displacement issues, whether in support of the return and re-integration of displaced or in addressing the needs of those in protracted displacement situations.